2021
DOI: 10.1136/bmjopen-2021-052547
|View full text |Cite
|
Sign up to set email alerts
|

Deprescribing intervention activities mapped to guiding principles for use in general practice: a scoping review

Abstract: ObjectiveTo identify and characterise activities for deprescribing used in general practice and to map the identified activities to pioneering principles of deprescribing.SettingPrimary care.Data sourcesMedline, EMBASE (Ovid), CINAHL, Australian New Zealand Clinical Trials Registry (ANZCTR), Clinicaltrials.gov, ISRCTN registry, OpenGrey, Annals of Family Medicine, BMC Family Practice, Family Practice and British Journal of General Practice (BJGP) from inception to the end of June 2021.Study selectionIncluded s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…For example, if a patient is taking opioid analgesics, their doctor would know that possible constipation is not an independent symptom but a side effect of the established medication [ 44 ]. There are many more approaches to reduce the risk of PP and of possibly dangerous DDIs [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, if a patient is taking opioid analgesics, their doctor would know that possible constipation is not an independent symptom but a side effect of the established medication [ 44 ]. There are many more approaches to reduce the risk of PP and of possibly dangerous DDIs [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was observed in previous studies [ 7 , 24 ]; Buranakitjaroen et al [ 24 ] found that about 10% of the patients who stopped their antihypertensive medications self-medicated by supplementing their antihypertensive medications due to anxiety or feeling unwell. Clinicians need to pay attention to patients' psychological status when deprescribing antihypertensive medication, which is one of the principles suggested by Coe et al [ 31 ]. One patient reported that the family’s concern about medication withdrawal was a primary reason to withdraw from the study.…”
Section: Discussionmentioning
confidence: 99%
“…The focus groups were analyzed thematically to identify barriers and facilitators to antidepressant deprescribing and inform the development of the first prototype of the WiserAD intervention. Second, a scoping review of 50 deprescribing interventions being used in general practice for any condition and medication was conducted in 2021 [44]. The scoping review identified key deprescribing activities and provided additional steps to create a self-sustaining deprescribing process loop for use in clinical practice.…”
Section: Phase 1: Eliciting and Formulating The Initial Program Theorymentioning
confidence: 99%